1984
DOI: 10.1111/j.1479-828x.1984.tb01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Contraceptive Method and Vaginal Flora

Abstract: This study was undertaken to assess whether the vaginal flora was affected by the method of contraception, and in particular as to whether the incidence of vaginal candidiasis increased when oral contraceptives were used. One thousand and two consecutive vaginal or cervical swabs from women attending a family planning centre were cultured. Candida albicans was isolated from 13% of women using no contraception, 16% using oral contraceptives, and from 9%, 19% and 18% of those using diaphragms, intrauterine contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…There was no significant difference in isolation percentage of Candida sp from test and control group of women aged 20–30 years which is consistent with the findings of Peddie, et al, [16] who reported no significant difference in contraceptives user and non-users when C. albicans was investigated. On the other hand, statistically significant difference in Candida sp compared to control was observed in women of age group 31–40 years which is not in agreement with the same study [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There was no significant difference in isolation percentage of Candida sp from test and control group of women aged 20–30 years which is consistent with the findings of Peddie, et al, [16] who reported no significant difference in contraceptives user and non-users when C. albicans was investigated. On the other hand, statistically significant difference in Candida sp compared to control was observed in women of age group 31–40 years which is not in agreement with the same study [16].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, statistically significant difference in Candida sp compared to control was observed in women of age group 31–40 years which is not in agreement with the same study [16]. This elaborates the importance of age factor as a crucial variable and determinant for vaginal ecology.…”
Section: Discussioncontrasting
confidence: 59%
“…Although diaphragm-spermicide use has been associated with E. coli vaginal colonization [20][21][22], the individual contributions of intercourse, spermicide use, and contraceptive method have been difficult to sort out. Our data show an incremental increase in the effects on E. coli vaginal colonization of spermicide use alone, cervical cap use, intercourse, and diaphragm-spermicide use.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies have shown that IUD use is associated with vaginal colonization of Gram-positive cocci [22] and E. coli [23], which are important pathogens related to AV [1]. The presence of the tail of the IUD in the endocervix or in the vagina may favor the growth of vaginal aerobic bacteria, which presumably play a role in the pathogenesis of AV.…”
Section: Discussionmentioning
confidence: 99%